Evaluation of Indigo carmine on hepatic ischemia and reperfusion injury - Rancan,Eduardo Alexandre (2020)
Abstract Purpose To evaluate the effects of treatment with Indigo Carmine (IC) on rat livers subjected to ischemia-reperfusion injury. Methods The animals were subdivided into 4 groups: 1.SHAM group(SH) - saline; 2.SHAM group with IC-2mg/Kg(SHIC); 3.IR group - rats submitted to ischemia and reperfusion with saline(IR); 4.IR group with IC-2mg/Kg(IRIC). The IR protocol consists of liver exposure and administration of drug or saline intravenously, followed by 60 minutes of ischemia and 15 of reperfusion. Liver samples were collected for biochemical analysis. Results State 3 of mitochondrial respiration showed a significant worsening of the IRIC group in relation to all others. State 4 showed a difference between IRIC and SHIC. The Respiratory Control Ratio showed statistical decrease in IR and IRIC versus Sham. The osmotic swelling showed significant difference between SHxIR; SHICxIRIC and SHxIRIC. There was a significant increase in ALT in the IRIC group in relation to all the others. Concerning the nitrate dosage, there was a decrease in the group treated with IC(IRxIRIC). There was no difference regarding the dosage of Malondialdehyde. Conclusion IC was not able to protect mitochondria from IR injury and proved to be a potentiating agent, acting in synergy with the IR injury promoting damage to the hepatocyte membranes.